2020
DOI: 10.4103/bc.bc_46_19
|View full text |Cite
|
Sign up to set email alerts
|

Role of vinpocetine in ischemic stroke and poststroke outcomes: A critical review

Abstract: Vinpocetine (VPN) is a synthetic ethyl-ester derivative of the alkaloid apovincamine from Vinca minor leaves. VPN is a selective inhibitor of phosphodiesterase type 1 (PDE1) that has potential neurological effects through inhibition of voltage-gated sodium channel and reduction of neuronal calcium influx. VPN has noteworthy antioxidant, anti-inflammatory, and anti-apoptotic effects with inhibitory effect on glial and astrocyte cells during and following ischemic stroke (IS). VPN is effective as adjuvant therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 84 publications
(79 reference statements)
1
28
0
Order By: Relevance
“…They also observed that most ofthe movement components of the reach areabnormal and those compensatory body movements provided the rotator movements to assist pronation and supination. The finding that rat fed with cassava diets produced a motor impairment is consistent with findings in animal konzo model [1,2] and human konzo patients [27][28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 86%
“…They also observed that most ofthe movement components of the reach areabnormal and those compensatory body movements provided the rotator movements to assist pronation and supination. The finding that rat fed with cassava diets produced a motor impairment is consistent with findings in animal konzo model [1,2] and human konzo patients [27][28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 86%
“…As well, patients with psychiatric disorders such as panic disorder are associated with significant reduction of hypothalamic orexin activations. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…As another potential, incomplete suppression of glutamatergic activity in the hippocampus may be necessary to investigate HCNP or HCNP-pp on hippocampal cognitive behavior. [ 4 ] Because other hippocampal molecules, such as vinpocetine, recover behavioral and memory outcomes through enhanced cholinergic neurotransmission, HCNP may also improve cognitive functions by targeting cholinergic activity,[ 35 ] which are also exhibited by stem cell administrations. [ 36 ] Further investigations are necessary to examine the functions of HCNP due to acetylcholine releases.…”
Section: Cholinergic Activitymentioning
confidence: 99%